Short-Term Reciprocity in Macaque’s Social Decision-Making - Ballesta, Sébastien; Reymond, Gilles; Duhamel, Jean-René (Frontiers in Behavioral Neuroscience, 2019)
Primates live in complex social environments, where individuals create meaningful networks by adapting their behavior according to past experiences with others. Although free-ranging primates do show signs of reciprocity, experiments in more controlled environments have mainly failed to reproduce such social dynamics. Hence, the cognitive and neural processes allowing monkeys to reciprocate during social exchanges remains elusive. Here, pairs of long-tailed macaques (Macaca fascicularis) took turns into a social decision task involving the delivery of positive (juice reward) or negative (airpuff) outcomes. By analyzing the contingencies of one partner’s past decisions on the other’s future decisions, we demonstrate the presence of reciprocity, but only for the exchange of negative outcomes. Importantly, to display this decisional bias, the monkey needs to witness its partner’s decisions, since non-social deliveries of the same outcome did not have such effect. Withholding of negative outcomes also predicted future social decisions, which suggest that the observed tit-for-tat strategy may not only be motivated by retaliation after receiving an airpuff but also by the gratefulness of not having received one. These results clarify the apparent dichotomy within the scientific literature of reciprocity in non-human primates and suggest that their social cognition comprise revenge and gratitude.